Time-of-Flight Measurements of Single-Electron Wave Packets in Quantum Hall Edge States - Kataoka, M; Johnson, N; Emary, C; See, P; Griffiths, JP; Jones, GAC; Farrer, I; Ritchie, David; Pepper, M; Janssen, TJBM (American Physical Society, 2019)
We report time-of-flight measurements on electrons traveling in quantum Hall edge states. Hot-electron wave packets are emitted one per cycle into edge states formed along a depleted sample boundary. The electron arrival time is detected by driving a detector barrier with a square wave that acts as a shutter. By adding an extra path using a deflection barrier, we measure a delay in the arrival time, from which the edge-state velocity v is deduced. We find that v follows 1=B dependence, in good agreement with the E × B drift. The edge potential is estimated from the energy dependence of v using a harmonic approximation.